Faculty Training for Online Teaching: Roles, Competences, Contents - Mansur F. Galikhanov; Gulnara F. Khasanova (Moscow Polytechnic University, 2019)
An important trend in higher education is an increasing use of digital technologies and an expansion of online-learning formats, which poses new challenges for university faculty to master the pedagogical competences in teaching online.Universities are forced to expand their educational activities in the online environment, and to involve an increasing number of teachers in the design and delivery of online courses. However, faculty members often do not have the necessary skills and competencies, and their experience in the use of digital technology is insufficient. Meanwhile, the success of online teaching depends not only on advanced methods and technologies, but first of all on the quality of faculty involved. An important issue is how teachers are trained to perform these tasks. To ensure the effectiveness of online education, the Institute of Further Professional Education of the Kazan National Research Technological University is developing approaches to training faculty for the transition to virtual learning environment. They should take into account factors, incentives and barriers affecting faculty's participation in online teaching, and analyze changes in the activities of teaching stuff in the online environment.The paper dwells on the foreign experience in training faculty for online teaching. We analyzed publications considering new roles and competencies of online teachers, barriers and motivations that encourage faculty to participate in online learning. The paper gives an overview of the content of foreign training courses aimed at the formation of a complex of subject, pedagogical and technological competences of faculty related to online teaching. The main goal of the analysis was to determine the core competencies of online teachers, so that to reflect them in the program of training faculty for teaching online.